Застосування стратегії узгодження концептів у теоретичній валідизації (на прикладі дослідження поведінкових практик студентів) - Дембіцький, С. (Социология: теория, методы, маркетинг, 2009)
The article is seeking to carry out two tasks: formulation of principles of theoretical validation; and description of the strategy of concept mapping as a procedure appli cab le at the initial stages of theoretical validation. The author singles out such principles of theoretical validation: socio-cultural relevance; concept-based repre sen ta tiveness and significance; operationalization; temporal and socio-spatial order liness; the complexity and cohesion of qualitative and quantitative approaches. The strategy of such a reconciliation of concepts is the structured process focused on the research conception or theme. It is a framework of producing conceptual map by the group of participants of the discussion. This method allows research participants to think more effectively as a collective subject without losing their individuality. The method is intended to particularize the basic idea of the prospective research and give it in detail. The concept mapping procedure is to be executed in six stages: preparation, statements (propositions) generation, statements (propositions) structurization, presentation of statements (propositions) on a conceptual map, interpretation, and application.